2017
DOI: 10.3329/jbsp.v12i1.33924
|View full text |Cite
|
Sign up to set email alerts
|

?-Tocopherol and Ketorolac on Pain in Long Evans Rats

Abstract: Background: Alpha-tocopherol (αT) is a form of vitamin E that is widely known to be one of the reactive oxygen species scavengers (ROS) and it has been shown to have analgesic effects in different animal and human studies. But comparison of these effects with similar effects of ketorolac tromethamine (KT) and their combination have not been established. Objective: To assess the effects of αT on pain and also compare them with those of the combinations of αT with KT in rat models.Methods: This experimental stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Interestingly, a recent study had revealed the potential of cinnamic acid to alleviate pain [63]; thus, it might help to support the present observations. In addition, GC-MS analysis of PECN revealed the presence of trimethylsilyl (TMS) derivatives of γ -tocopherol, α -tocopherol, and lupeol of which α -tocopherol [64] and lupeol [65] have been shown to exert antinociceptive activity whereas γ -tocopherol has been reported to enhance the anti-inflammatory potential of acetylsalicylic acid [66]. These bioactive compounds might also contribute to the observed antinociceptive activity of PECN.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a recent study had revealed the potential of cinnamic acid to alleviate pain [63]; thus, it might help to support the present observations. In addition, GC-MS analysis of PECN revealed the presence of trimethylsilyl (TMS) derivatives of γ -tocopherol, α -tocopherol, and lupeol of which α -tocopherol [64] and lupeol [65] have been shown to exert antinociceptive activity whereas γ -tocopherol has been reported to enhance the anti-inflammatory potential of acetylsalicylic acid [66]. These bioactive compounds might also contribute to the observed antinociceptive activity of PECN.…”
Section: Discussionmentioning
confidence: 99%